Feasibility of chitosan thin film and hybrid chitosan/silica thin film for the mitigation of toxic Alexandrium minutum - Ibrahim, N.H.; Iqbal, Anwar; Mohammad Noor, Normawaty; M.R., Roziawati; Sreekantan, Srimala; A.S., Zulkipli (Elsevier, 2022)
Harmful Algal Bloom (HAB) has been a growing issue worldwide for the past few decades, posing harm to aquatic ecosystems and drinking water quality. Therefore, this research aims to investigate the feasibility of a chitosan thin film and hybrid chitosan/silica thin film prepared via a one-pot synthesis method to mitigate toxic algae cells, Alexandrium minutum. The film-forming solution was synthesised by stirring chitosan and sodium silicate solutions obtained from rice husk ash (RHA). The films were neutralised with NaOH and distilled water and finally dried at room temperature. The thin films were characterised using attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy and scanning elec- tron microscopy (SEM). The SEM analysis indicates that the new thin film’s surface was smooth compared to the used thin films. The mitigation of A. minutum was carried out for 72 h. The chitosan film achieved 18.1 % removal of A. minutum at 72 h, whereas 23.8% of the algae was removed when the hybrid chitosan/ silica thin film was used. Digital microscopic imaging showed that the algae cells were adsorbed on the chitosan film’s surface ruptured, whereas the adsorbed cells on the hybrid films were preserved. The ATR- FTIR analysis of the used film indicates the presence of the algae cells, which changes the functional group of the film. The film can be separated easily from the seawater and exhibit good biodegradable properties as it degrades after being buried in the soil for one month.